A Refinement of the Processes Controlling Dissolved Copper and Nickel Biogeochemistry: Insights From the Pan‐Arctic. Issue 5 (10th May 2022) - Jensen, Laramie T.; Cullen, Jay T.; Jackson, Sarah L.; Gerringa, Loes J. A.; Bauch, Dorothea; Middag, Rob; Sherrell, Robert M.; Fitzsimmons, Jessica N.
Abstract: Recent studies, including many from the GEOTRACES program, have expanded our knowledge of trace metals in the Arctic Ocean, an isolated ocean dominated by continental shelf and riverine inputs. Here, we report a unique, pan‐Arctic linear relationship between dissolved copper (Cu) and nickel (Ni) present north of 60°N that is absent in other oceans. The correlation is driven primarily by high Cu and Ni concentrations in the low salinity, river‐influenced surface Arctic and low, homogeneous concentrations in Arctic deep waters, opposing their typical global distributions. Rivers are a major source of both metals, which is most evident within the central Arctic's Transpolar Drift. Local decoupling of the linear Cu‐Ni relationship along the Chukchi Shelf and within the Canada Basin upper halocline reveals that Ni is additionally modified by biological cycling and shelf sediment processes, while Cu is mostly sourced from riverine inputs and influenced by mixing. This observation highlights differences in their chemistries: Cu is more prone to complexation with organic ligands, stabilizing its riverine source fluxes into the Arctic, while Ni is more labile and is dominated by biological processes. Within the Canadian Arctic Archipelago, an important source of Arctic water to the Atlantic Ocean, contributions of Cu and Ni from meteoric waters and the halocline are attenuated during transit to the Atlantic. Additionally, Cu and Ni in deep waters diminish with age due to isolation from surface sources, with higher concentrations in the younger Eastern Arctic basins and lower concentrations in the older Western Arctic basins. Plain Language Summary: The trace metals copper and nickel are key elements involved in the biological and chemical cycles present in the ocean that help fuel the algae forming the base of the marine food web. The Arctic Ocean is heavily influenced by inputs from land including river discharge and continental sediments, and it has limited exchange with other oceans. We found that dissolved copper and nickel have Arctic distributions unique from the rest of the global ocean and are also surprisingly linearly correlated in the Arctic. We carefully compared them to each other and to other chemical tracers in order to identify the processes that control their distributions. We found that copper and nickel concentrations are highest in Western Arctic surface waters, due to riverine discharge for both metals, and also continental shelf sources of nickel. In deeper waters, copper and nickel concentrations are low and constant, unlike in other ocean basins. Also, unique to the Arctic, biological cycling was not a controlling factor for copper and nickel behavior, and interactions of these metals with particles were also less than observed elsewhere. Overall, the Arctic was an ideal case study for the importance of different ocean processes on controlling marine copper and nickel. Key Points: Dissolved Cu and Ni share a unique linear correlation in the Arctic Ocean, with high surface water and low deep water concentrations Cu is sourced primarily from rivers, while Ni is also sourced from sediments on the Chukchi Shelf Concentrations of both are lower in Western than in Eastern Arctic deep waters, and both are attenuated in the Canadian Arctic Archipelago